ANALISIS KEBUTUHAN BAHAN AJAR SAINS TERPADU BERBANTUAN AUGMENTED REALITY - Nurfadillah, Nurfadillah; Gani, Hamsu Abdul; Abdul Hakim, Abdul Hakim (Indonesian Journal of Educational Technology, 2023)
The implementation of learning at SMP Hangtuah Makassar during the COVID pandemic required adjustment to the teaching and learning process. Teachers had to innovate and adapt to meet learning needs and achieve objectives despite challenging conditions. To overcome this, teachers as facilitators must develop up-to-date learning materials to improve quality, increase acceptance, and boost desire to learn in and outside classrooms. Teachers need to develop technology-based teaching materials that can be utilized anywhere, anytime as alternatives to traditional materials. Given these conditions, further examination is necessary regarding the needs analysis for developing integrated science teaching materials assisted by augmented reality technology at Hangtuah Junior High School Makassar. Analysis of student needs in integrated science learning for 7th grade identified that science subject materials and application were sufficiently integrated. Then, analysis of media needs in integrated science learning showed strong interest in using teaching materials with augmented reality technology during learning